Adjuvant chemotherapy in patients with completely resected non-small cell lung cancer - Pirker, Robert (Transl Lung Cancer Res, 2014)
Adjuvant chemotherapy has been established as a standard for patients with completely resected non-small cell lung cancer (NSCLC). Adjuvant chemotherapy increased the 5-year survival rates by 4% to 15% within randomized trials and, based on a meta-analysis of five cisplatin-based trials, by 5.4%. Adjuvant chemotherapy consists of a cisplatin-based doublet, preferentially cisplatin plus vinorelbine. Future improvements in outcome of adjuvant therapy are expected by customized chemotherapy and the integration of targeted therapies or immunotherapy.